E-knjige - Eržen, Matjaž (Knjižnica, 2011)
Purpose: To research the situation in the field of electronic books (e-books) offered by the libraries of the University of Ljubljana, and the problems they are facing up to the collection management of these materials. Methodology/approach: An analysis based on data accessible through the web sites of some libraries and the DiKUL portal (Digital library of the University of Ljubljana), completed by the data provided by some libraries, is presented. Results: The results and above all the findings about dilemmas the librarians at the University of Ljubljana are dealing with confirm similar problems as stated in the foreign professional literature. There are different kinds of business models, problems with the usage statistics, bibliographic record's quality and access to library materials. Research limitation: A disrupted organizational structure of the University of Ljubljana library network and consequently a disunited approach to the acquisition and management of e-books as well as a large number of administrators aggravate the gathering of research data and represent obstacles to a more comprehensive collection planning and development. Originality/practical implications: The findings enable a better overview of e-books and initialize a more unified system and activities to provide better access to e-books.
Keywords: e-knjige; elektronske knjige; bibliografski zapisi; MARC; COMARC; statistični podatki; knjižnice; University of Ljubljana; Univerza v Ljubljani